2012
DOI: 10.3354/meps09679
|View full text |Cite
|
Sign up to set email alerts
|

Bivalve fauna and distribution in the Amur River estuary—a warm-water ecosystem in the cold-water Pacific region

Abstract: The understanding of the processes regulating the species richness and diversity in estuarine ecosystems is a fundamental problem of ecology. The Amur River estuary is characterised by high summer water temperatures (up to 20−21°C) anomalous for the cold-water northwestern Pacific region. We hypothesized that the warm-water Amur estuary greatly influences the species richness of this cold-water region, contributing to the far northward spread of warm-water macrobenthic species. We investigated the fauna and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
3
0
4
Order By: Relevance
“…In the northwestern Pacific, in contrast to the Atlantic, many thyasirid species appear to be exclusively abyssal and hadal species ( Okutani, Fujikura & Kojima, 1999 ; Fujikura et al, 2002 ; Okutani, 2003 ; Sasaki, Okutani & Fujikura, 2005 ; Kamenev, 2015 , 2018 , 2019 ). The shelf and bathyal zones of this region have been well explored ( Scarlato, 1981 ; Kamenev, 1995 , 2013 ; Okutani, 2000 ; Kamenev & Nekrasov, 2012 ). However, these studies did not reveal thyasirid species which were later found at abyssal depths of the deep-sea basin of the Sea of Okhotsk and on oceanic plains, and on the slopes and bottom of oceanic trenches.…”
Section: Discussionmentioning
confidence: 99%
“…In the northwestern Pacific, in contrast to the Atlantic, many thyasirid species appear to be exclusively abyssal and hadal species ( Okutani, Fujikura & Kojima, 1999 ; Fujikura et al, 2002 ; Okutani, 2003 ; Sasaki, Okutani & Fujikura, 2005 ; Kamenev, 2015 , 2018 , 2019 ). The shelf and bathyal zones of this region have been well explored ( Scarlato, 1981 ; Kamenev, 1995 , 2013 ; Okutani, 2000 ; Kamenev & Nekrasov, 2012 ). However, these studies did not reveal thyasirid species which were later found at abyssal depths of the deep-sea basin of the Sea of Okhotsk and on oceanic plains, and on the slopes and bottom of oceanic trenches.…”
Section: Discussionmentioning
confidence: 99%
“…Максимум биомассы формировался M. balthica (рис. 3) и соответствовал пространственному расположению пика биомассы этого вида, зафиксированному по данным предшествующих авторов [Kamenev, Nekrasov, 2012]. В центральной части общая биомасса распределялась в диапазоне от 10 до 40 г/м 2 , у западного берега значения наиболее низкие -преимущественно до 10 г/м 2 .…”
Section: результаты и обсуждениеunclassified
“…Состав и распределение двустворчатых моллюсков в проливе Невельского В работах же, посвященных фауне двустворчатых моллюсков, прилегающих к прол. Невельского районов [Дуленина, 2013;Kamenev, Nekrasov, 2012], M. balthica конкретно указывается в ряду доминирующих видов.…”
Section: результаты и обсуждениеunclassified
See 2 more Smart Citations